Optimal Cutoff Scores for Alzheimer's Disease Using the Chinese Version of Mini-Mental State Examination Among Chinese Population Living in Rural Areas. (December 2016) - Yang, Zhao; Holt, Hunter K.; Fan, Jin-Hu; Ma, Li; Liu, Ying; Chen, Wen; Como, Peter; Zhang, Lin; Qiao, You-Lin
To explore the optimal cutoff score for initial detection of Alzheimer's Disease (AD) through the Chinese version of Mini-Mental State Examination (CMMSE) in rural areas in China, we conducted a cross-sectional study within the Linxian General Population Nutritional Follow-up study. 16, 488 eligible cohort members participated in the survey and 881 completed the CMMSE. Among 881 participants, the median age (Interquartile range) was 69.00 (10.00), 634 (71.92%) were female, 657 (74.57%) were illiterate, 35 (3.97%) had 6 years of education or higher, and 295 (33.48%) were diagnosed with AD. By reducing the CMMSE criteria for illiterate to 16 points, primary school to 19 points, and middle school or higher to 23 points, the efficiency of Chinese version of Mini-Mental State Examination can be significantly improved for initial detection of AD in rural areas in China, especially in those nutrition deficient areas.